1996
DOI: 10.2337/diab.45.2.209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperglycemia on Nerve Conduction and Structure Is Age Dependent

Abstract: The nerve conduction velocity (NCV) of nondiabetic male Wistar rats continues to increase until approximately 26 weeks of age. Rats made hyperglycemic at 6 weeks of age manifest reduced NCV by 10 weeks of age and show morphological differences in the sciatic tibial nerve after 5 months of hyperglycemia when compared with age-matched controls. Fiber diameter, myelin width, and the number of large myelinated fibers were decreased in the tibial nerves of the hyperglycemic animals. Rats made hyperglycemic at 26 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 11 publications
2
21
0
1
Order By: Relevance
“…Our results showed that there is a definite reduction in MNCV and SNCV by 3 years of diabetes with demonstrable morphometric changes at 5 years. Similar changes of nerve conduction have been reported in rats but as diabetes is usually induced in a phase of rapid body growth, it is difficult to distinguish the effects of diabetes from that of retarded maturation in this model [5,14]. This problem has been minimized in our study; the longevity of baboons allowed the induction of diabetes to be at an age when the increase in nerve conduction had plateaued, as shown by the measurements on the controls (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our results showed that there is a definite reduction in MNCV and SNCV by 3 years of diabetes with demonstrable morphometric changes at 5 years. Similar changes of nerve conduction have been reported in rats but as diabetes is usually induced in a phase of rapid body growth, it is difficult to distinguish the effects of diabetes from that of retarded maturation in this model [5,14]. This problem has been minimized in our study; the longevity of baboons allowed the induction of diabetes to be at an age when the increase in nerve conduction had plateaued, as shown by the measurements on the controls (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…In the sciatic nerves of diabetic rats, there are obvious morphological changes within 5 months of induction [18,35]. Interpretation of these results needs, however, to take into account that these rats are often extremely hyperglycaemic and in the rapid stage of nerve growth [14,36]. In humans, sural nerve biopsy specimens taken in the later stages of diabetes, usually when neuropathy is a clinical problem, have provided information on structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While that study showed dose-dependent protection of hind limb digital sensory NCV, motor NCV in sciatic tibial-interosseous and caudal nerves was not significantly altered. However, in their model, diabetes was induced in young (8 weeks of age) rats and part of the NCV deficit depends on blunting of the axial growth and maturation of nerve fibres [28,29] so that motor NCV deficits are relative to age-matched rather than onset control values. In contrast, in our mature rat model using proximal sciatic nerve fibres, motor NCV changes are relative to onset controls and there is little further maturation effect [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It must be stressed, however, that those authors used the same dose of streptozotocin but in considerably younger animals (mean weight of 250 gr and 75 days of age). Considering that peripheral nerves of rats are more suscetible to morphological and physiological changes until the 26 th week of age 27 , it is possible that the myenteric plexus of younger rats is more sensitive to experimental diabetes than that of mature ones.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%